Differences in In‐Hospital and Post‐Discharge Ischemic Stroke Care According to Prestroke Functional Status - Paul M. Wechsler; Eva A. Mistry; Heidi Sucharew; David J. Robinson; Robert Stanton; Felipe de los Rios La Rosa; Jason Mackey; Simona Ferioli; Stacie L. Demel; Elisheva R. Coleman; Adam Jasne; Sabreena Slavin; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Limited data exist regarding differences in ischemic stroke care across the care continuum between patients with and without prestroke disability. We investigated differences in in‐hospital and postdischarge ischemic stroke cause evaluation and treatment between patients with and without prestroke disability using population‐based data in the United States. Methods We ascertained all adult patients (≥18 years) hospitalized with acute ischemic stroke within the Greater Cincinnati/Northern Kentucky population between January 1, 2015, and December 31, 2015. We used univariate analyses and logistic regression to compare differences in acute ischemic stroke reperfusion therapies, stroke cause evaluation, prescription of secondary stroke prevention treatments, and rehabilitation between patients with prestroke disability (modified Rankin Scale score ≥2) and those without prestroke disability (modified Rankin Scale score 0–1). Results Of 2476 ischemic stroke patients, 1326 (53%) had prestroke disability. Prestroke disability was associated with lower odds of receiving thrombolysis (adjusted odds ratio [aOR], 0.43 [95% CI, 0.28–0.68], P<0.01) and endovascular thrombectomy (aOR, 0.32 [95% CI, 0.13–0.78], P<0.01). Patients with prestroke disability were less likely to receive complete in‐hospital stroke cause evaluation (aOR, 0.48 [95% CI, 0.33–0.69], P<0.01) and there were small differences in antiplatelet (84% versus 87%) and statin therapy (80% versus 86%) prescribed at discharge. Those with prestroke disability were more likely to receive in‐hospital (aOR, 2.6 [95% CI, 2.11–3.21], P<0.01) and postdischarge rehabilitative therapies (aOR, 2.27 [95% CI, 1.86–2.77], P<0.01). Conclusion Further research into factors driving medical decision‐making for patients with prestroke disability is needed to optimize the entire spectrum of ischemic stroke care for this population.